Two new species of Parameletus Bengtsson, 1908 (Ephemeroptera: Siphlonuridae), and notes on other species from the Far East of Russia - Tiunova, Tatiana M. (Zootaxa, 2008)
Two new species of Parameletus are described, increasing the number of species known from Far East of Russia to four: P. chelifer Bengtsson 1908, P. minor (Bengtsson 1909), and the new species P. ensiformis and P. arcuatus. Both new species are known from male imagines. P. minor is first recorded for the Southern Far East. Illustrations and a key for the male imagines of the known species of Parameletus from Russian Far East are provided. Distributional data are presented.